A transição do modelo de educação antiga grega para o cristão : Clemente de Alexandria e a inspiração na paideia helênica - França, Maria Lenilda Caetano (2022)
The research presents the transition from the model of education constituted in Ancient Greece to the one that emerged with the advent of Christianity. In the first, we find its base composed of three great "paideias": the Homeric, the Sophistic and the Socratic-Platonic. These, as we want to prove, directly influence the Christian educational process. We identified as primary sources Plato's conceptions, because he was one of the greatest critics of the educational models advocated by Homer and the Sophists, as well as those of Clement of Alexandria, regarded by the literature as the pioneering theologian in the construction of the Christian paideia. This is a theoretical research oriented by a set of concepts, namely: education, justice, pedagogue, pedagogy, so that the exegesis of such set clarifies the two theoretical proposals and identifies the continuities and ruptures of the authors studied. Thus, we had as a central problem: does the Christian paideia present originality when compared to previous Greek educational models? This question unfolds in the following questions: what are the central ideas of the education promoted in the Homeric, Socratic-Platonic and Sophistic periods? What is the place of the Socratic-Platonic paideia in view of the promotion of the city as a space of the just order? What are the fundamental ideas of the Christian educational proposal conceived by Clement of Alexandria and to what extent was the slave pedagogue a fruitful inspiration for the organization of the educational foundations of such a project? In order to glimpse the answers, we describe the scope, the plan, and the treatment of the educational proposals present in the three great Greek paideias and the influences for Clement's Christian model; we investigate the insertion of the figure of the slave pedagogue conveyed in these periods; we analyze how Clement reconfigures the slave pedagogue, making him divine, to launch a project of Christian education; and, finally, we resume the contribution of Plato and Clement of Alexandria to an idea of education in the ancient world, in order to highlight their singularities and establish a new interpretation that Christianity proposes of the ancient tradition, contributing to the field of the history of pedagogical ideas. We recognize the link between the Platonic thought and that of the Alexandrian in what concerns the objective of education: to make men excellent in virtue and in the values of the soul, having as a distinctive aspect the faith propounded by Clement.